ÉTICA E VIRTUDE: A FORMAÇÃO HUMANA NA ESCOLA - Mateus de Freitas Barreiro; Alonso Bezerra de Carvalho (Universidade do Oeste Paulista, 2016)
This article aims to investigate the ethics of Aristotle's philosophy, through the elucidation of virtue in order to understand how does the human formation in the current school. Ethics is not just limited to a philosophical conceptual system on how to steer based on the perpetuation of moral values, but above all, ethics is a habit which is the subject to guide actions aimed at the good of others and collective equity. We conclude that school problems should cover both the ethical dimension as epistemic. However due to the difficulty in achieving these goals in school, students have been increasingly forwarded by educators to health professionals, in which the practice of standardization through medicalization, is increasingly replacing the ethical responsibility of different actors within and out of school.